Perfluorinated organics regulating Li2O2 formation and improving stability for Li–oxygen batteries. Issue 24 (24th February 2021) - Wang, Yuling; Bai, Fan; Wang, Aiping; Cui, Zhonghui; Wang, Da; Shi, Siqi; Zhang, Tao
Abstract : Perfluorotributylamine, an artificial blood, is introduced into lithium–oxygen batteries due to its excellent oxygen solubility, achieving superior high capacity and long stability. Abstract : Lithium–oxygen batteries have a high theoretical capacity, but they are still far from meeting the capacity required for practical applications. In this study, we systematically investigate the synergistic effect of perfluorotributylamine (PFTBA) as an additive in a TEGDME-based electrolyte to optimize the electrochemical performance of Li–O2 batteries. PFTBA promotes cyclic Li2 O2 growth, and the discharge capacity is increased to 9548.7 mA h g −1 . Moreover, the hydrophobicity of PFTBA can aid in the protection of the lithium anode against corrosion as it remains stable during cycling. The Li–O2 battery exhibited enhanced cycling stability (200 cycles) as a consequence. This study reveals that PFTBA increases the capacity and provides more possibilities for the application of perfluorinated chemicals in Li–O2 batteries.